2012
DOI: 10.1080/02642069.2011.575130
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the scales: recovering from service failures depends on the psychological distance of consumers

Abstract: The purpose of this research is to enhance knowledge about service recovery by investigating the feelings of psychological distance in the relationship between customers' perceptions of service recovery efforts of the perceived justice dimensions (distributive, procedural, and interactional justice) and attitudinal responses such as satisfaction with service recovery effort and trust in the firm. The results of structural equation modelling analyses suggested that consumers who had positive justice perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…Thus, product quality (Ulaga and Eggert, 2006), order delivery (Ulaga and Eggert, 2006) and personnel training (Conca et al , 2004), as benefits of the core axis, were measured based on existing scales adapted accordingly to our study context, as well as product cost (Ritter and Walter, 2012) and switching cost (Barry and Terry, 2008). For the access axis, the measures for the benefits of customization (Homburg et al , 2011), service support (Ulaga and Eggert, 2006) and social support (Wang et al , 2012), together with service failure cost (Lii et al , 2012) and low interaction cost (Homburg et al , 2011) incorporated indicators with minor adaptations of existing scales. The same did not occur in the case of “low quality cost” construct, which we developed based on the work of Yang (2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, product quality (Ulaga and Eggert, 2006), order delivery (Ulaga and Eggert, 2006) and personnel training (Conca et al , 2004), as benefits of the core axis, were measured based on existing scales adapted accordingly to our study context, as well as product cost (Ritter and Walter, 2012) and switching cost (Barry and Terry, 2008). For the access axis, the measures for the benefits of customization (Homburg et al , 2011), service support (Ulaga and Eggert, 2006) and social support (Wang et al , 2012), together with service failure cost (Lii et al , 2012) and low interaction cost (Homburg et al , 2011) incorporated indicators with minor adaptations of existing scales. The same did not occur in the case of “low quality cost” construct, which we developed based on the work of Yang (2008).…”
Section: Methodsmentioning
confidence: 99%
“…In terms of access costs, the following may be identified: service failure cost (Lii et al , 2012; Harrison-Walker, 2012) deriving from the manufacturer’s inability to meet customer expectations; low interaction cost (Homburg et al , 2011), stemming from imbalances between the interests and actions of the manufacturer’s communication systems, namely task or interaction; and low quality cost (Yang, 2008; Cheah et al , 2011), which is the difference between the actual cost of the product/service and the cost that would be incurred if the product/service were not defective.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Repeat patronage intention looks at the customer's intentions to continue with a product and/or an intention to increase the scale and scope of this relationship [42]. Meanwhile, regarding attitudinal dimension, we adopted word-of-mouth (WOM) communication as it has been confirmed by other scholars that WOM is a significant factor that influences consumer choices [44,45]. Word of mouth is when consumers' interest in a product or service is reflected in their daily dialogues.…”
Section: Re-patronage and Word Of Mouth (Wom)mentioning
confidence: 99%
“…[59,60]). From the study on Zara case, Royo-Vela and Casamassima [12] have demonstrated that the higher the level of participation in a virtual brand community, the higher the positive word-of-mouth advertising towards the brand around which the community is developed.…”
Section: Wom and Repurchase Intentionmentioning
confidence: 99%